Chaenothecopsis neocaledonica sp. nov.: The first resinicolous mycocalicioid fungus from an araucarian conifer - Rikkinen, Jouko; Tuovila, Hanna; Beimforde, Christina; Seyfullah, Leyla; Perrichot, Vincent; Schmidt, Alexander R (Phytotaxa, 2014)
A new resinicolous species of the genus Chaenothecopsis (Ascomycota, Mycocaliciales) is described from resin of Agathis ovata in New Caledonia. Chaenothecopsis neocaledonica sp. nov. is the first mycocalicioid fungus to be described from the exudates of Southern Hemisphere conifers of the family Araucariaceae. It is easily distinguished from related Northern Hemisphere species by its larger ascospores and unique capitulum structure.